Showdown. (Economist, 2016)
The article offers the author's insights on the computer program AlphaGo written by researchers at artificial intelligence (AI) software house DeepMind in London, England and ancient game Go invented by the mythical First Emperor of China. Topics discussed include the rules of the game, the difficulty of the game, and the use of same technologies as those older programs by AlphaGo.